Telepresence-enabled archaeological survey and identification of SS Coast Trader, Straits of Juan de Fuca, British Columbia, Canada. (April 2018) - Delgado, James P.; Cantelas, Frank; Symons, Lisa C.; Brennan, Michael L.; Sanders, Richard; Reger, Evan; Bergondo, Deanna; Johnson, Donald L.; Marc, Jacques; Schwemmer, Robert V.; Edgar, Lea; MacLeod, Duncan
Abstract: During a June 2016 mission aboard E/V Nautilus, a previously undocumented multibeam sonar target thought to be a shipwreck was investigated at 165 m depth off Victoria, BC. The target was the wreck believed to be SS Coast Trader, torpedoed and sunk on 7 June 1942 by the Imperial Japanese Navy submarine I-26 . Utilizing a Remotely Operated Vehicle (ROV), a several-hour long survey dive was conducted to characterize the target, and was led remotely via telepresence from the Inner Space Center in Rhode Island. The observations made during this dive confirmed this wreck is Coast Trader . This report summarizes the history, loss, survey and observations on the potential for the wreck to pollute the surrounding marine environment. This project was led by the Ocean Exploration Trust (OET), in partnership with the National Oceanic and Atmospheric Administration (NOAA), Office of National Marine Sanctuaries (ONMS), NOAA Pacific Marine Environmental Lab (PMEL), and funded by the NOAA Office of Ocean Exploration and Research (OER).